2021
DOI: 10.3390/ijerph182211992
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Palliative Care in Cancer Patients in Spain

Abstract: Background: The COVID-19 pandemic outbreak has severely affected healthcare organizations worldwide, and the provision of palliative care (PC) to cancer patients has been no exception. The aim of this paper was to analyse the levels of health care provided by the Clinical Management Unit for PC in Córdoba (Spain) for cancer patients. Method: a retrospective cohort study was conducted. It analyzed the PC internal management database including all cancer patients treated in the period of 2018–2021. Results: 1967… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Delivery of palliative and supportive care to hospital inpatients escalated during the pandemic; in the case of cancer patients, this trend may, at least in part, have reflected decreased utilization of hospice/PCU care [ 52 ]. Notably, an increase in admissions to a general hospital in-patient unit for the express purpose of symptom palliation was observed, as well as an increase in palliative care consult requests for inpatients on general medical wards [ 53 , 54 ]. In the latter context, 39% of patients were assessed in-person, and 61% by virtual means [ 51 ▪ ], though this ratio varied by institution and jurisdiction.…”
Section: Impact Of Covid-related Resource Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delivery of palliative and supportive care to hospital inpatients escalated during the pandemic; in the case of cancer patients, this trend may, at least in part, have reflected decreased utilization of hospice/PCU care [ 52 ]. Notably, an increase in admissions to a general hospital in-patient unit for the express purpose of symptom palliation was observed, as well as an increase in palliative care consult requests for inpatients on general medical wards [ 53 , 54 ]. In the latter context, 39% of patients were assessed in-person, and 61% by virtual means [ 51 ▪ ], though this ratio varied by institution and jurisdiction.…”
Section: Impact Of Covid-related Resource Limitationsmentioning
confidence: 99%
“…As noted, referrals made to the palliative care service from the inpatient wards in general hospitals increased during the pandemic (up to 42%, in one report from Spain); at the same time, there was a corresponding decrease in referrals from the outpatient/primary care setting [ 53 ]. Overall, these authors reported no change in the total number of cancer patients treated by palliative and supportive care services during the pandemic, compared with the prepandemic period.…”
Section: Impact Of Covid-related Resource Limitationsmentioning
confidence: 99%
“…The comprehensive data concerning the impact of COVID-19 on cancer care in Europe reported that the pandemic had caused about a 20% decrease in the referral of newly diagnosed patients to oncological care [35]. This same observation was made about access to palliative care [36].…”
Section: Discussionmentioning
confidence: 77%
“…Several patients have reported decreased quality of life and depression because of the COVID‐19 epidemic (Beltran‐Aroca et al, 2021; Dhavale et al, 2020; Mishra et al, 2022; Nyblom et al, 2022; Yennurajalingam et al, 2022; Yildiz Kabak et al, 2021). This change may be related to fear of infection with COVID‐19 (Mishra et al, 2022), fear of disease progression (Yildiz Kabak et al, 2021), and fear of incomplete treatment (Dhavale et al, 2020).…”
Section: Resultsmentioning
confidence: 99%